Give Me Your Best Shot! Diffusion of Complete versus Booster Covid-19 Vaccines across US Counties - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper compares drivers of full COVID-19 vaccinations and booster doses across U.S. counties. Booster doses are contingent upon someone receiving the primary doses, and the risk attitudes and propensities to get vaccinated may be different across individuals, along with the supply chain differences across the primary and booster doses. Results show that new covid cases do not significantly impact vaccinations, while supply chain aspects via pharmacies had a positive impact. The effects of income, race, age, and education were largely consistent with intuition. Further, political ideologies mattered, while government decentralization did not. There were differences in the signs, magnitudes, and significance of the influence of some drivers across primary versus booster doses. Robustness checks include using alternative estimation techniques and examining differences across counties with low- and high vaccination rates. Policy implications are discussed.
Keywords: I18; I11; H75; H11; D72; 330; Covid-19; vaccination; pandemic; booster; government; supply chain; pharmacies; political ideology; risk attitudes; county; United States